Doświadczanie przestrzeni jako konstruowanie kulturowego obrazu. Przykład Bałkanów I Syberii - Ewertowski, Tomasz (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
The paper analyses the process of the experiencing of space as constructing image. In the first part of the paper the main theoretical assumptions are presented. They are based on the postcolonialism theory, Erazm Kuźma’s semiological idea of the unessential nature of the term ‘East’, and Jeep Leerssen’s concept of image. The main idea is that the process of the experiencing of space always produces an image of space which consists more cultural than geographical information. This image corresponds to the ideological categories of its progenitors. In the second part of the paper two examples of the analysed process are described. The author demonstrates different phenomena connected with images of the Balkans and Siberia. This part focuses on such concepts as ‘balkanism’ (according to Maria Todorova), ‘the reproduction of orientalism’ (according to Milica Bakić-Hayden), and the mataphorization of image (the romantic image of Siberia was also used to describe Western culture).
The experiencing of space as constructing image. Examples of the Balkans and Siberia
Keywords: Bałkany; Balcans; bałkanizm; balcanism; mentalna geografia; mental geography; orientalizm; orientalism; postkolonializm; postcolonialism; Syberia; Siberia